Mathematics Curriculum Reforms Around the World The 24th ICMI Study - Shimizu, Yoshinori; Vithal, Renuka (New ICMI Study Series, 2023)
This Open Access volume by the International Commission on Mathematical Instruction (ICMI) is an outcome of the ICMI Study 24 and gives a status-quo of school mathematics reform around the world and what we can learn from this movement. Each theme and section of the book offers descriptions and analyses of multiple case studies in different countries and contexts, along with opportunities to compare, contrast and learn from these diverse experiences. The volume provides a synthesis and meta-analysis of the different historical, geographical and global aspects of school mathematics reforms and explores in which way curricula are elaborated, proposed, changed, and reorganized. It offers a more informed and comprehensive analysis of the roles of different actors and of the many aspects influencing and shaping mathematics curriculum reforms that are taking or have taken place. It also explores the possibilities and means to tackle a curricular reform in the current scenario we live in and how to unfold future developments. This book will be of interest to practitioners and scholars with an interest in school mathematics curriculum reforms. It will also be a useful resource to those involved in school mathematics curriculum reform initiatives by providing current information about the curriculum changes that are taking place in respect of content, teacher education, educational materials, and a range of implementation challenges across diverse contexts.